Developing an Augmented Reality Immersive Learning Design (AILeaD) Framework: A Fuzzy Delphi Approach - Zain, Farah Mohamad; Sailin, Siti Nazuar; Kasim, Marini; Abdul Karim, Abdul Malek; Zameri, Nurfarah Najlaa (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The use of augmented reality as a teaching aid among teachers is becoming more widespread. So, it is a must to create a holistic framework of augmented reality in order to enhance the teaching and learning context. Therefore, the purpose of this study is to develop an augmented reality immersive learning design (AILeaD) framework by using the Fuzzy Delphi Technique. The objective of this research is to gain experts’ consensus in building and identifying constructs and elements as well as their place in the AILeaD framework. The Fuzzy Delphi Technique is used as a systematic method to evaluate, verify as well as to make a decision in modifying all needed constructs and elements in order to create the AILeaD framework through the consensus of the experts. The research questionnaire is divided into three sections which are technology skills, instructional designs and type of augmented reality applications in a total of 36 items and using the Likert-7point scale. The sample of this research consists of 10 experts from educational technology, teaching technology, augmented reality and model development. The finding showed that the experts agreed and approved all of the constructs and elements where the three conditions were fulfilled which are the item value is less than or same with the threshold value (d) < 0.2, experts’ consensus percentage exceeded 75% and defuzzification value per item exceeded α-cut = 0.5. This study could contribute to the educational policy that focuses on the development of teaching quality with the improvement of existing skills among educators through the innovation and utilization of technology in the teaching and learning context. This is in line with Malaysia Education Blueprint known as Shift 7 (2013 – 2025) where it leverages the utilization of ICT to enhance the quality of education in Malaysia. The implication of this study is to make the AILeaD framework as a guideline for teachers, lecturers and instructional designers in producing the teaching aids in accordance with augmented reality and taking Gagne Nine Events, Cognitive Theory of Multimedia Learning dan Revised Bloom Taxonomy into account.